A reproducible endothelial-state contrast with limited bulk prognostic robustness in hepatocellular carcinoma - Si-yuan Tan; Lan-hui Qin; Wenqing Liang; Rui Song; Pei-yin Chen; Weihui Xu; Guanzhen Zeng; Yu Zhang; Liling Long (Functional & Integrative Genomics, 2026)

Engineered aptamer-confined hydrogel for label-free detection of heavy-metal ions with enhanced interference tolerance - Long Bai; Xiuxiu Wu; Lei Huang; Haohao Chen; Jinsong Yu; Ziqing Ye; Min Yuan; Hui Cao; Liling Hao; Fengqin Yin; Tai Ye; Fei Xu (Food Chemistry, 2026)

Corrigendum to “Long-term exposure to fine particulate matter constituents and the prognosis of oral cancer patients: A prospective study in Southeastern China” [J Hazard Mater 487 (2025) 137304] - Peng Hu; Liling Shen; Ge Chen; Weiyi Yang; Yanmei Ji; Baochang He; Hualiang Lin (Journal of Hazardous Materials, 2026)

A multi-dimensional modified deep learning framework for predicting potential creep-type landslides based on geological data - Yue Liu; Peihua Xu; Chen Cao; Liling Jin; Bo Han; Rongchen Ma; Chensi Li (Earth Science Informatics, 2026)

Correction to: Long-Term Monochromatic Light Exposure Does Not Alter Modular Chromatic Representation in the Visual Cortex of Rhesus Monkeys - Wenqing Zhu; Ye Liu; Xiaoxiao Chen; Liling Qian; Wei Wang; Leilei Zou; Yiliang Lu; Rui Liu (Neuroscience Bulletin, 2026)

Concurrent biodegradation of tylosin and tilmicosin by a novel Paracoccus versutus 4-B-2 - Zhengyan Chen; Anqi Liu; Junzhe Cui; Chunhui Liu; Huijuan Li; Ziyi Quan; Yaxu Liu; Xiao Guo; Xiaoyu Wang; Liling Fan; Bo Wang (Journal of Hazardous Materials, 2026)

Long-Term Monochromatic Light Exposure Does Not Alter Modular Chromatic Representation in the Visual Cortex of Rhesus Monkeys - Wenqing Zhu; Ye Liu; Xiaoxiao Chen; Liling Qian; Wei Wang; Leilei Zou; Yiliang Lu; Rui Liu (Neuroscience Bulletin, 2026)

Beyond Single Stressors: Integrated Physiological and Transcriptomic Responses of Argopecten irradians Exposed to Polystyrene and Toxic Dinoflagellates - Weijia Song; Jianguo Ding; Liling Guan; Jie Ma; Huixuan Liu; Hongli Zhang; Yangjun Chen; Kaiqin Jiang (Oceans, 2026)
Toxic dinoflagellate blooms and microplastics are widespread coastal pollutants. In this study, the scallop, Argopecten irradians, was selected as an experimental organism to systematically investigate the single and combined toxic effects of polystyrene (PS) and the toxic dinoflagellate, Alexandrium pacificum. The results showed that both PS and algal cells could be ingested by A. irradians. The survival rate of A. irradians remained above 90% in both the single and combined treatment groups, indicating that 1 mg/L PS and 1500 cells/mL A. pacificum cells did not pose a serious threat to scallop survival in the short term. However, CAT, SOD, and GSH-ST activities, as well as MDA content, were all elevated in the combined treatment group. Transcriptomic analysis further revealed that A. pacificum primarily affected immune-related pathways, whereas PS might interfere with endocrine function through the release of additives. Combined exposure to PS and A. pacificum induced more complex synergistic effects, reflected in the metabolic stress of exogenous substances, and the disruption of developmental and homeostasis regulatory pathways. This study provides important theoretical support for assessing the threats posed by composite coastal pollution to aquaculture and marine ecological security.

Multilayered regulatory control of compound leaf development - Liangliang He; Liling Yang; Weiyue Zhao; Jianghua Chen (Current Opinion in Plant Biology, 2026)

Corrigendum to “sulfated hyaluronic acid/collagen-based biomimetic hybrid nanofiber skin for diabetic wound healing: Development and preliminary evaluation” [carbohydrate polymers, volume 334, 15 June 2024, 122025] - Yuanmeng Zhou; Weibin Jia; Jiexue Bi; Meng Liu; Liling Liu; Hang Zhou; Guofeng Gu; Zonggang Chen (Carbohydrate Polymers, 2026)

TMC6 Protects Against Ischemic Neuronal Injury by Activating Rap1/Rac1 Signaling to Restore Mitochondrial Dynamics and Mitophagy - Xuemei Quan; Huo Liang; Haiyin Long; Xiawei Wang; Liling Feng; Xia Zhou; Yuan Chen; Yanhua Li; Xiaofeng Li (Molecular Neurobiology, 2026)

Balancing human development and environmental protection: Evidence from the Yangtze River Economic Belt ecological and environmental protection policy - Liling Zhu; Fei Chen; Huiqiang Zhang; Yi Li (Journal of Cleaner Production, 2025)

Emulsion gels with dual antioxidant and antibacterial functions for optimized β-carotene Delivery: Utilizing phenolic acid-modified agarose - Liling Fu; Yi Ru; Qinglin Hong; Huifen Weng; Yonghui Zhang; Jun Chen; Anfeng Xiao; Qiong Xiao (Food Hydrocolloids, 2025)

Ontogenetic niche segregation and its implications for mercury levels in Japanese anchovy from the high seas of the northwestern Pacific Ocean as revealed by fatty acid analysis - Long Chen; Zhenfang Zhao; Guanyu Hu; Liling Zhang; Bilin Liu; Xinjun Chen (Journal of Fish Biology, 2025)
Japanese anchovy ( Engraulis japonicus ) is a small pelagic fish that is frequently targeted by commercial fisheries. Japanese anchovy plays a crucial role as a vital link between primary and higher‐order consumers. The elemental mercury in Japanese anchovy muscles easily bioaccumulates and is transmitted to top predators. We investigated the variation in the diets and mercury accumulation of Japanese anchovy in the high seas of the northwestern Pacific Ocean. We measured the amounts of mercury and fatty acids in the muscles of 149 Japanese anchovy specimens that were obtained from the open seas of the northwestern Pacific Ocean (39°2′ N ~ 42°30′ N, 154°02′ E ~ 161°29′ E) between June and July 2021. The results revealed that the monounsaturated fatty acid (MUFA) and polyunsaturated fatty acid (PUFA) contents significantly decreased and then increased with the growth of Japanese anchovy ( p

Contact-dependent antagonism is mediated by a T7SSb toxin effector–immunity protein pair via ADP-ribosylation - Hongxin Guan; Huan Wu; Mengrou Gan; Jing Zhang; Jiajun Wang; Siyao Liu; Shuyue Chen; Yindi Jiao; Fan Li; Shiqing Huang; Sihuang Lin; Hongwei Chen; et al. (Science Bulletin, 2025)

Passion fruit peel pectin improves glucose and lipid metabolism in high-fat diet-induced obesity through gut microbiota and insulin sensitivity regulation - Ying Ju; Liling Huang; Hailing Luo; Yongcai Huang; Xianya Huang; Ge Chen; Jie Gui; Shengli Lin; Xuzhou Liu; Liu Yang (Food Bioscience, 2025)

Analysis of the molecular karyotype of Kengyilia grandiglumis on the Qinghai-Tibet Plateau via sequential FISH and GISH - Ruijuan Liu; Liling Jiang; Yijun Zhong; Yue Wu; Demei Liu; Wenjie Chen (Genetic Resources and Crop Evolution, 2025)

Mediation role of gut microbiota in the association between ambient fine particulate matter components and cardiovascular disease: Evidence from a China cohort - Shaokun Yang; Rui Yu; Fen Yang; Jiawei Li; Lele Wang; Gonghua Wu; Liling Chen; Tingting Yang; Zhuoma Duoji; Yanjiao Wang; Xufang Gao; Yuanyuan Liu (Environmental Research, 2025)

Unlocking phosphorus recovery from microalgae biomass: The enhanced transformation and release of phosphorus species - Liling Zhou; Jiabin Chen; Yajie Qian; Yalei Zhang; Egshiglen Batjargal; Baigal-Amar Tuulaikhuu; Xuefei Zhou (Water Research, 2025)

A multiplex RT‑PCR detection system for pepper co-infection by three potyviruses - Tiyuan Xia; Liling Mo; Xinyang Chen; Wang Wang; Pengyu Liu; Xingmei Tao; Xuan Yi; Zuqin Qiao; Yongfu Zhang; Xiaoqin Li (Journal of General Plant Pathology, 2025)

Long-term exposure to fine particulate matter constituents and the prognosis of oral cancer patients: A prospective study in Southeastern China - Peng Hu; Liling Shen; Ge Chen; Weiyi Yang; Yanmei Ji; Baochang He; Hualiang Lin (Journal of Hazardous Materials, 2025)

Innovation-driven cities: Reconciling economic growth and ecological sustainability - Fei Chen; Liling Zhu; Huiqiang Zhang; Yi Li (Sustainable Cities and Society, 2025)

Climate change and human activities drive the warm-season rooftop solar photovoltaic potential in the Chinese Chengdu-Chongqing urban agglomeration - Yilin Li; Lijun Liu; Tianyu Zhang; Youjia Liang; Zhenghong Chen; Liling Chu; Chao He (Sustainable Cities and Society, 2025)

Legumes reduce the effects of salt stress on co-existing grass - Liling Liu; Ziyan Chen; Xiaomei Gou; Lingcao Hou; Chenglong Liang; Huan Jiao; Weibo Kong; Liping Qiu; Xiang Wang; Xiaorong Wei (Journal of Environmental Management, 2025)

Spatial single-cell maps reveal ST6GAL1 promoting ovarian cancer metastasis - Lan-hui Qin; Zijian Jiang; Chongze Yang; Rui Song; Pei-yin Chen; Weihui Xu; Guanzhen Zeng; Jin-yuan Liao; Liling Long (Glycoconjugate Journal, 2025)

Bi2O2Se nanosheets coated with rosmarinic acid for colon-targeted treatment of inflammatory bowel disease - Jiahu Yao; Yang Yang; Hu Zhao; Chuanming Wang; Liang Jin; Tengyun Long; Wei Huang; Xiang Zhan; Xin Li; Xin Chen; Jinhu Xie; Bin Wu; et al. (Chemical Engineering Journal, 2025)

Effects of diet and habitat on Hg levels in Japanese anchovy in the high seas of the northwestern Pacific Ocean - Long Chen; Guanyu Hu; Zhenfang Zhao; Bilin Liu; Xinjun Chen; Liling Zhang (Marine Pollution Bulletin, 2024)

Investigating the impact of watershed and local environmental variables on the spatial distribution, composition and functional diversity of benthic algal communities in the upper Red River Basin, China - Kejian He; Xuekai Feng; Changming Chen; Yu Han; Xiaoxiao Ji; Yangyidan He; Liling Yang; Yuan He; Xingcan Chen; Liqin Yan (Aquatic Sciences, 2024)

Protective Effect of CXCR7 Against Hypoxia/Reoxygenation Injury in Renal Tubular Epithelial Cells - Ping Meng; Chunli Liu; Jingchun Li; Ping Fang; Liling Chen (Cell Biochemistry and Biophysics, 2024)
Acute kidney injury (AKI) is a multifactorial syndrome with complex pathophysiology and prognosis. Ischaemia‒reperfusion injury (IRI) is a major cause of induced AKI. The aim of this study was to investigate the effect of upregulated CXCR7 expression on renal tubular epithelial cell apoptosis induced by hypoxia/reoxygenation (H/R). HK-2 cells were divided into three groups: control group (pcDNA3.1), hypoxia/reoxygenation + pcDNA3.1 group (H/R+pcDNA3.1) and CXCR7 overexpression + hypoxia/reoxygenation group (H/R+ Flag-CXCR7). Protein levels of renal tubular epithelial cell injury-, apoptosis- and autophagy-related markers were assessed by qRT‒PCR, Western blotting, flow cytometry (FCM), immunofluorescence and transmission electron microscopy (TEM). In addition, HK-2 cells were treated with the autophagy inhibitor 3-MA and divided into 3 groups: control group, 3-MA + pcDNA3.1 group, and 3-MA + Flag-CXCR7 group. Changes in autophagy and apoptosis in renal tubule epithelial cells were assessed by Western blotting and FCM. Compared with those in the control group, the protein and mRNA expression levels of CXCR7 in HK-2 cells were significantly lower under H/R conditions. Under H/R conditions, CXCR7 overexpression in HK-2 cells significantly downregulated the expression of NGAL. Moreover, CXCR7 overexpression significantly decreased H/R-induced cleaved PARP-1 and cleaved Caspase 3 levels, increased the level of the antiapoptotic protein BCL-2 and the autophagy-related molecules ATG5 and LC3B II, and significantly inhibited the expression of P62. Autophagy flow and TEM also showed that CXCR7 significantly promoted autophagy. CXCR7 significantly alleviated the 3-MA-induced inhibition of autophagy and increase in apoptosis. Upregulated CXCR7 expression can inhibit renal tubular epithelial cell apoptosis and damage by regulating autophagy. In conclusion, CXCR7 is a promising target for the prevention and/or treatment of AKI.

First report of chilli veinal mottle virus infecting Lactuca sativa in China - Yue Chen; Gui Gao; Ting Ting Li; Jie Chen; Yue Yan Yin; Jing Zhong; Liling Zhao; Yi Cao; Ming Ding (Journal of Plant Pathology, 2024)

Active packaging coating based on agarose grafted with benzoic acid derivatives: Preparation, characterization and application in fish preservation - Liling Fu; Yi Ru; Jinming Ye; Qinglin Hong; Huifen Weng; Yonghui Zhang; Jun Chen; Anfeng Xiao; Qiong Xiao (Food Hydrocolloids, 2024)

First report of pod pepper vein yellows virus infecting Solanum nigrum L. in China - Yongfu Zhang; Pengyu Liu; Liling Mo; Xinyang Chen; Wang Wang; Xingmei Tao; Xiaoqin Li (Journal of Plant Pathology, 2024)

Sulfated hyaluronic acid/collagen-based biomimetic hybrid nanofiber skin for diabetic wound healing: Development and preliminary evaluation - Yuanmeng Zhou; Weibin Jia; Jiexue Bi; Meng Liu; Liling Liu; Hang Zhou; Guofeng Gu; Zonggang Chen (Carbohydrate Polymers, 2024)

Long-term exposure to fine particulate matter constituents in relation to chronic kidney disease: evidence from a large population-based study in China - Yucen Dai; Jianzhong Yin; Sicheng Li; Jiawei Li; Xinyu Han; Quzong Deji; Ciren Pengcuo; Leilei Liu; Zhimiao Yu; Liling Chen; Linshen Xie; Bing Guo; et al. (Environmental Geochemistry and Health, 2024)

M6PR interacts with the HA2 subunit of influenza A virus to facilitate the fusion of viral and endosomal membranes - Yuzhen Hu; Li Jiang; Guangwen Wang; Yangming Song; Zhibo Shan; Xuyuan Wang; Guohua Deng; Jianzhong Shi; Guobin Tian; Xianying Zeng; Liling Liu; Hualan Chen; et al. (Science China Life Sciences, 2024)

Associations between metal(loid) exposure with overweight and obesity and abdominal obesity in the general population: A cross-sectional study in China - Tianran Shen; Liling Zhong; Guiyuan Ji; Baolan Chen; Mengfan Liao; Lvrong Li; Huiming Huang; Jiajie Li; Yuan Wei; Shan Wu; Zihui Chen; Wenjun Ma; et al. (Chemosphere, 2024)

In vivo tracing of triazole pesticides in Chinese cabbage via a novel solid-phase microextraction fiber - Yingming Duan; Yiquan Huang; Liling Huang; Zhangmin Xiang; Jian Liu; Shuqin Liu; Zhuo Chen (Food Control, 2024)

CMTM 6 promotes the development of thyroid cancer by inhibiting NIS activity through activating the MAPK signaling pathway - Xin Chen; Hao Shen; Huifang Liu; Liling Tan; Nuobei Zhang (Functional & Integrative Genomics, 2024)

Cobalt-induced apoptosis of cochlear organotypic cultures and HEI-OC1 cells is mediated by Dicer - Xuexin Lin; Liling Li; Jia Luo; Dan Chen; Jingqian Tan; Peng Li (NeuroToxicology, 2024)

Differential responses of macroinvertebrates and phytoplankton to river health status in different habitats - Kejian He; Changming Chen; Yangyidan He; Xuekai Feng; Hong Tang; Liling Yang; Yuan He; Wenna Lyu (Aquatic Sciences, 2024)

Arthrospira cell residue valorization: A study on protein hydrolysate production by limited enzymatic hydrolysis - Kefan Ouyang; Qian Chen; Hexiang Xie; Qin Zhang; Liling Tao; Hua Xiong; Yulan Du; Jiangang Yan; Xinliang Mao; Qiang Zhao (Food Bioscience, 2023)

Optimizing directional recovery of high-bioavailable phosphorus from human manure: Molecular-level understanding and assessment of application potential - Yao Xu; Nan Li; Libin Yang; Tongcai Liu; Shaoze Xiao; Liling Zhou; Dapeng Li; Jiabin Chen; Yalei Zhang; Xuefei Zhou (Water Research, 2023)

Development of a toughened and antibacterial Poly(lactide acid) (PLA) with preserved strength by elemental sulfur-based bio-renewable dynamically crosslinked elastomers - Xiaojie Chen; Ruanquan Zhang; Yixuan Mao; Liling Zhong; Peiyao Lin; Qizhe Deng; Botuo Zheng; Hang Shen; Zhiming Feng; Huagui Zhang (Chemical Engineering Journal, 2023)

Temporal Variations of Water Quality and Pollution Source Structures Over 15 Years Reflect Effects of Water Pollution Control in the Upper Tuojiang River Basin, China - Xiaocong Liu; Hongjin Tong; Qiang Chen; Yao Wei; Zhuang Liu; Liling Zhang; Jingyi Zhang (Water, Air, & Soil Pollution, 2023)

Broad humoral immunity generated in mice by a formulation composed of two antigens from the Delta variant of SARS-CoV-2 - Yadira Lobaina; Rong Chen; Edith Suzarte; Panchao Ai; Vivian Huerta; Changyuan Tan; Liz Alvarez-Lajonchere; Yang Liling; Alexis Musacchio; Ricardo Silva; Gerardo Guillén; Jiang Zaixue; et al. (Archives of Virology, 2023)

Adverse effects of triclosan exposure on health and potential molecular mechanisms - Xuhui Chen; Li Mou; Jiayuan Qu; Liling Wu; Changjiang Liu (Science of The Total Environment, 2023)

A critical review of solid peroxides in environmental remediation and water purification: From properties to field applications - Liling Zhou; Yajie Qian; Jiabin Chen; Yalei Zhang; Xuefei Zhou (Chemical Engineering Journal, 2023)

Nanocellulose-enhanced smart film for the accurate monitoring of shrimp freshness via anthocyanin-induced color changes - Liling Li; Wenxiu Wang; Mengdan Zheng; Jianfeng Sun; Zhizhou Chen; Jie Wang; Qianyun Ma (Carbohydrate Polymers, 2023)

Continued evolution of the Eurasian avian-like H1N1 swine influenza viruses in China - Fei Meng; Yan Chen; Zuchen Song; Qiu Zhong; Yijie Zhang; Chuanling Qiao; Cheng Yan; Huihui Kong; Liling Liu; Chengjun Li; Huanliang Yang; Hualan Chen (Science China Life Sciences, 2023)

Tumor suppressor LHPP suppresses cell proliferation and epithelial-mesenchymal transition in hepatocellular carcinoma cell lines - Lunkun Ma; Huifang Sun; Xichao Xu; Ying Chen; Lu Zhang; Shun Li; Liling Tang (Journal of Physiology and Biochemistry, 2022)

Genetic and biological characteristics of the globally circulating H5N8 avian influenza viruses and the protective efficacy offered by the poultry vaccine currently used in China - Pengfei Cui; Xianying Zeng; Xuyong Li; Yanbing Li; Jianzhong Shi; Conghui Zhao; Zhiyuan Qu; Yanwen Wang; Jing Guo; Wenli Gu; Qi Ma; Yuancheng Zhang; et al. (Science China Life Sciences, 2022)
The H5N8 avian influenza viruses have been widely circulating in wild birds and are responsible for the loss of over 33 million domestic poultry in Europe, Russia, Middle East, and Asia since January 2020. To monitor the invasion and spread of the H5N8 virus in China, we performed active surveillance by analyzing 317 wild bird samples and swab samples collected from 41,172 poultry all over the country. We isolated 22 H5N8 viruses from wild birds and 14 H5N8 viruses from waterfowls. Genetic analysis indicated that the 36 viruses formed two different genotypes: one genotype viruses were widely detected from different wild birds and domestic waterfowls; the other genotype was isolated from a whopper swan. We further revealed the origin and spatiotemporal spread of these two distinct H5N8 virus genotypes in 2020 and 2021. Animal studies indicated that the H5N8 isolates are highly pathogenic to chickens, mildly pathogenic in ducks, but have distinct pathotypes in mice. Moreover, we found that vaccinated poultry in China could be completely protected against H5N8 virus challenge. Given that the H5N8 viruses are likely to continue to spread in wild birds, vaccination of poultry is highly recommended in high-risk countries to prevent H5N8 avian influenza.

Pandemic threat posed by H3N2 avian influenza virus - Yaping Zhang; Conghui Zhao; Yujie Hou; Yan Chen; Fei Meng; Yichao Zhuang; Liling Liu; Yasuo Suzuki; Jianzhong Shi; Guohua Deng; Hualan Chen (Science China Life Sciences, 2021)

CircRNA expression profiling and bioinformatics analysis indicate the potential biological role and clinical significance of circRNA in influenza A virus-induced lung injury - Jiajia Wang; Yanbing Zhang; Fengfeng Zhu; Liling Chen; Yao Wei; Qingqing Zhu; Junhong Jiang; Jian-an Huang; Qiang Guo; Xinjing Yang (Journal of Biosciences, 2021)

Temperature changes between neighboring days and childhood asthma: a seasonal analysis in Shanghai, China - Xiaoning Lei; Lijuan Liu; Renjie Chen; Cong Liu; Jianguo Hong; Lanfang Cao; Yanming Lu; Xiaoyan Dong; Xinchang Chen; Xiangwei Qiu; Min Xia; Bo Ding; et al. (International Journal of Biometeorology, 2021)

DNAH17 is essential for rat spermatogenesis and fertility - Liling Chen; Jiamin Ouyang; Xueqing Li; Xueshan Xiao; Wenmin Sun; Shiqiang Li; Lin Zhou; Yuandong Liao; Qingjiong Zhang (Journal of Genetics, 2021)

Introduction of a multicenter online database for non-metastatic breast cancer in China - Yaping Yang; Jieqiong Liu; Min Peng; Fengxi Su; Xiaoming Xie; Zhenzhen Liu; Jundong Wu; Wei Wei; Dongxian Zhou; Weiwen Li; Ailing Zhang; Guosen Su; et al. (Science China Life Sciences, 2020)

Liangyi Gao extends lifespan and exerts an antiaging effect in Caenorhabditis elegans by modulating DAF-16/FOXO - Liling Zeng; Chen Sun; Zhong Pei; Tianchan Yun; Shaoyi Fan; Simei Long; Tengteng Wu; Ziwen Chen; Zhimin Yang; Fuping Xu (Biogerontology, 2019)

Glycosylation and an amino acid insertion in the head of hemagglutinin independently affect the antigenic properties of H5N1 avian influenza viruses - Chunyang Gu; Xianying Zeng; Yangming Song; Yanbing Li; Liling Liu; Yoshihiro Kawaoka; Dongming Zhao; Hualan Chen (Science China Life Sciences, 2019)

Comparison of breast-conserving surgery and mastectomy in early breast cancer using observational data revisited: a propensity score-matched analysis - Kai Chen; Zihao Pan; Liling Zhu; Tingting Hu; Min Peng; Weijuan Jia; Fengxi Su; Shunrong Li; Erwei Song (Science China Life Sciences, 2018)

Correction to: Strategies of Drug Transporter Quantitation by LC-MS: Importance of Peptide Selection and Digestion Efficiency - Buyun Chen; Liling Liu; Hoangdung Ho; Yuan Chen; Ze Yang; Xiaorong Liang; Jian Payandeh; Brian Dean; Cornelis E. C. A. Hop; Yuzhong Deng (The AAPS Journal, 2018)

Epidemiological and genetic characteristics of the fifth avian influenza A(H7N9) wave in Suzhou, China, from October 2016 to April 2017 - Zefeng Dong; Yu Xia; Xuerong Ya; Liling Chen; Cheng Liu; Ruyan Wang; Qiang Shen (Virus Genes, 2018)

Strategies of Drug Transporter Quantitation by LC-MS: Importance of Peptide Selection and Digestion Efficiency - Buyun Chen; Liling Liu; Hoangdung Ho; Yuan Chen; Ze Yang; Xiaorong Liang; Jian Payandeh; Brian Dean; Cornelis E. C. A. Hop; Yuzhong Deng (The AAPS Journal, 2017)

Circulating CD34+ cells are elevated in neonates with respiratory distress syndrome - Yuanyuan Qi; Liling Qian; Bo Sun; Chao Chen; Yun Cao (Inflammation Research, 2010)

Characterization of An Avian Influenza Virus of Subtype H7N2 Isolated from Chickens in Northern China - Yanbing Li; Chengjun Li; Liling Liu; Hongwei Wang; Chuanbin Wang; Guobing Tian; Robert G. Webster; Kangzhen Yu; Hualan Chen (Virus Genes, 2006)